ANALISIS KECOCOKAN STRATEGI BNI CONTACT CENTER SETELAH ADANYA PERUBAHAN ORGANISASI Studi Kasus di PT BNI Tbk - , Rizki Aditya Wardhana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is a case study in the Contact Center Division of BNI (BNI Call) at PT BNI Tbk . The purpose of this study was to determine the suitability of the strategies used by BNI Call is in conformity with the wishes of the management of PT BNI Tbk . This study based on two framework on the book Crafting and Executing Strategy (Thompson , Strickland , Gamble : 2010) , namely : How well are acceptable under the strategy of the company's condition ? And if this strategy is able to significantly improve the performance of the company ? To answer the first question , researchers used the internal and external environment analysis using the SWOT analysis and SWOT matrix quadrants . As for the second question of the thought in the book Crafting and Executing Strategy , using the results of comparative analysis of the performance of BNI Call during the period 2007 to 2011 , with the observations from 2009 to 2011. Where assessment is considered a good performance when up to six targets are: Increased service satisfaction ratings BNI Call by Carre - CSSL Survey ranking , increase service level indicators of service ( Ease of accessibility and service Call BNI ) where the target is 80 % per 20 seconds ( the average industry banking call center ) , a low level of efficiency in the operation of the call center (cost per call ) , increasing agent BNI call Quality call , drop Average call Handling Time HR BNI and the increased use of IVR call BNI system . The results obtained based on SWOT analysis and matrix quadrant indicates that BNI Call is at a weak internal position but have the opportunity to thrive in an external environment . So the strategy is a strategy that supported the changes . the results of the second Framework for analyzing, BNI Call performance improved on external survey ranking Carre - CSSL , decrease operating costs per call , average handling time decreased HR , and improving the quality of human resources phone. The results of this study may be relevant to answer the question whether it is the right strategy BNI Call ? Call BNI strategy needs to be revised , especially the organizational structure , IT systems and Call Center Human Resources.